2018
DOI: 10.20858/sjsutst.2018.100.5
|View full text |Cite
|
Sign up to set email alerts
|

A decision support tool for a walkable integrated neighbourhood design using a multicriteria decision-making method

Abstract: Growing concern about transportation emissions and energy security has persuaded urban professionals and practitioners to pursue non-motorized urban development. They need an assessment tool to measure the association between the built environment and pedestrians' walking behaviour more accurately. This research has developed a new assessment tool called the Walkable Integrated Neighbourhood Design (WIND) support tool, which interprets the built environment's qualitative variables and pedestrians' perceptual q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Among all the studies, only 10 (36%) reported decision support processes that existed in digital formats. A range of methods were employed in the development of these decision frameworks, models, and tools, including stakeholder engagement [45][46][47][48], literature reviews [49][50][51][52], primary data collection [43,44,53], and secondary data analysis [54][55][56][57][58][59][60][61]. Some studies combined methods, such as utilizing both literature reviews and primary data [62,63], both literature reviews and secondary data [64][65][66], both stakeholder engagement and secondary data [67], and both primary and secondary data [68].…”
Section: Description Of Tools and Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all the studies, only 10 (36%) reported decision support processes that existed in digital formats. A range of methods were employed in the development of these decision frameworks, models, and tools, including stakeholder engagement [45][46][47][48], literature reviews [49][50][51][52], primary data collection [43,44,53], and secondary data analysis [54][55][56][57][58][59][60][61]. Some studies combined methods, such as utilizing both literature reviews and primary data [62,63], both literature reviews and secondary data [64][65][66], both stakeholder engagement and secondary data [67], and both primary and secondary data [68].…”
Section: Description Of Tools and Frameworkmentioning
confidence: 99%
“…Nevertheless, only one of these, namely, the community health framework [56], provided a comprehensive integration of multiple aspects of health benefits, albeit without considering the environmental and economic dimensions of trees and greenspace benefits. Another tool that exclusively concentrated on health benefits was the WIND tool for assessing walkability [53]. Importantly, the remaining 16 out of 18 frameworks/models/tools in this category extended their scope to incorporate at least one aspect of environmental or economic benefits alongside the health dimension.…”
Section: Health Benefitsmentioning
confidence: 99%